Pengaruh Penggunaan Media Pop-up Book Berbasis Kearifan Lokal Suku Sasambo terhadap Hasil Belajar IPAS Siswa Kelas IV di SDN 32 Cakranegara - Destri Pitrianingsih; Khairun Nisa; Ilham Handika (Mataram University, 2026)
This research is motivated by the low learning outcomes of students in science and the limited use of innovative and contextual learning media in elementary schools. In addition, the potential of SASAMBO local wisdom as a learning resource that can make learning more contextual and meaningful has not been optimally utilized in the learning process. This study aims to determine the effect of the use of Pop-up book media based on Sasambo local wisdom on the learning outcomes of fourth-grade students in Sdn 32 Cakranegara. This study uses a quantitative approach with a quasi-experimental design and an unequal control group design. The research population is all 56 fourth-grade students in Sdn 32 Cakranegara, consisting of 28 students in each class: Class IV A as the experimental class and Class IV B as the control class. The sampling technique uses saturated sampling. The research instrument consists of pre-test and post-test questions, as well as an observation sheet for learning implementation. Data analysis using normality test, homogeneity test, independent sample t-test, and effect size test using SPSS version 25 for Windows. The results showed that the average pre-test score for the experimental class was 56.9 and increased to 94.4 in the post-test. Meanwhile, the control class obtained an average pre-test score of 54.4 and a post-test score of 79.0. The results of the independent sample t-test showed a significance value (2-tailed) of 0.000 <0.05, so H0 was rejected and Ha was accepted. This indicates a significant effect of the use of pop-up book media based on Sasambo local wisdom on the science learning outcomes of fourth-grade students at Sdn 32 Cakranegara. The calculation of the effect size using Cohen's D also showed a large category, which indicates that pop-up book media has a strong influence in improving student learning outcomes. Based on the results of this study, it can be concluded that the use of pop-up book media based on Sasambo local wisdom is effective in improving the science learning outcomes of fourth-grade students at Sdn 32 Cakranegara.